INVITRO VALIDATION OF ANTIMICROBIAL ACTIVITY OF BIOACTIVE COMPOUNDS FROM THERAPEUTIC PLANTS - ABIRAMI. M; KAYATHIRI. S.S; VIDYA.P; FARHANA SHIREEN.A; RAJALAKSHMI.V (The Bioscan, 2024)
Herbal plants have historically served as vital alternative treatments, especially in developing countries, due to their natural antiseptic properties and role in traditional medicine. This research paper explores the significance of medicinal plants in drug development, noting that a substantial proportion of populations in underdeveloped regions still rely on herbal remedies. The extraction process involved the use of various solvents including methanol, chloroform, and acetone to obtain plant extracts from C. roseus, M. oleifera, E. alba, and C. papaya. The antibacterial activity of the plant extracts were evaluated using the agar well diffusion method, revealing their effectiveness against different bacterial strains. Notably, the maximum zones of inhibition varied for each plant extract, demonstrating varying levels of activity against specific bacterial cultures. Furthermore, the minimal inhibitory concentration (MIC) of the plant extracts was determined, which ranges from 100μg to 1000μg. The MIC values for the herbal extracts of C. roseus against S.aureus and E. coli were successfully identified, highlighting their inhibitory effects on bacterial growth. Additionally, phytochemical screening indicated the presence of bio-active compounds such as saponin, terpenoid, flavonoid, alkaloid, and oil in the plant extracts. Finally, chemical characterization of the plant extract of C. roseus using Fourier Transform Infrared Spectroscopy (FT-IR) revealed the presence of functional groups including alkanes, aliphatic amines, carboxylic acid, and aromatic compounds.